Growing Teratoma Syndrome: A Rare Outcome. (4th January 2021) - Rebelo, João; Moreira, Francisco; Morgado, Margarida; Preto, Ana Sofia; Madureira, António
Abstract : Growing teratoma syndrome is a rare condition described in both testicular and ovarian cancer. We present a case of a 26-year-old male with known mixed germ cell tumor which exhibited new and progressive secondary lesions during imaging surveillance, later to be histologically characterized as teratomas.